Pemberian ASI terhadap Komposisi Tubuh pada Bayi Prematur: A Systematic Review: Breastfeeding on Body Composition in Premature Infants: A Systematic Review - Dzulkifli, Achmad; Nadhiroh, Siti Rahayu; Syahdana, Achidah Nur (Amerta Nutrition, 2024)
Background: Premature newborns have a higher susceptibility to metabolic syndrome and cognitive impairment compared to infants born at full term. Breast-feeding is advised as a natural source of nutrition for premature newborns and as a cost-effective approach to decrease illness and financial strain. Assessing preterm children's growth and body composition upon leaving the hospital is crucial and requires great attention due to its sensitivity and significance in determining future care. Objectives: This study aimed to compare the body composition of preterm infants who were fed breast milk against formula.  Methods: This study employed a systematic survey approach, which involved the use of fifteen exploratory diaries covering the period from 2013 to 2023. The search terms employed were "breast-feeding", "body composition", OR "preterm infants".    Discussions: Breast-feeding preterm infants has a positive correlation with the deposition of body fat-free mass. This helps maintain healthy body composition, prevent obesity, prevent loss of brain cell development, and promote optimal growth instead of formula feeding. The body composition of premature newborns undergoes alterations during breast-feeding at ages that correspond to their expected due dates, which may contribute to the mitigation of risk factors associated with metabolic syndrome. Conclusions: Breast-feeding preterm infants results in slower weight gain compared to formula feeding. However, it is more effective in repairing body composition by increasing body fat-free mass, which leads to better metabolic outcomes and neurodevelopment. The care of preterm newborns places a high priority on promoting breastfeeding and providing breastfeeding support.